MEDIA EFFECTS OF AFFAIRS IN â€œLAYANGAN PUTUSâ€ SERIES (STUDY ON SINGLE WOMEN IN BANDUNG CITY) - Alicia Achma Syafir; Maulana Rezi Ramadhana (Syntax Literate, 2022)
This study discusses the effects of the media on infidelity in the layangan putus series. The purpose of this research is to find out the media effect of layangan putus series on the affair of unmarried women in Bandung. This study uses a qualitative research method with a naturalistic approach in which the researcher wants to describe how the effect of the serial media effect on the affair of women who have never been married in Bandung. Data collection techniques were carried out by observing and interviewing women who had never been married in Bandung. The results of the study show that to prevent infidelity, unmarried women experience emotional feelings and feelings of anxiety resulting from the media effect of "Layangan Putus". Media effects occur when a person is exposed to something that takes place continuously. In this case, the media effect that is grown is an affective effect which results in a feeling of suspicion towards a partner, the emergence of a feeling of fear of marriage, and a feeling of fear of cheating after marriage. In the process of evaluating relationships, unmarried women and their partners communicate with each other by informing them of the impact of the affair. In this case, the behavioral effect produced in the series of "Layangan Putus"is to form a possessive partner attitude by monitoring the partner's behavior, always monitoring the partner's behavior, always confirming the partner's words, and having the desire to check the partner's cell phone.